2019
DOI: 10.3168/jds.2018-15949
|View full text |Cite
|
Sign up to set email alerts
|

Milk polar lipids modulate lipid metabolism, gut permeability, and systemic inflammation in high-fat-fed C57BL/6J ob/ob mice, a model of severe obesity

Abstract: Dynamic interactions between lipid metabolism, gut permeability, and systemic inflammation remain unclear in the context of obesity. Milk polar lipids, lipids derived from the milk fat globule membrane, could positively affect the aforementioned obesity-related endpoints. This study aimed to test the hypotheses that milk polar lipids will reduce gut permeability, systemic inflammation, and liver lipid levels, and differentially affect the hepatic expression of genes associated with fatty acid synthesis and cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 67 publications
(81 reference statements)
1
25
0
Order By: Relevance
“…Previous studies have found strong correlations between plasma SM and IL‐6. [ 18 ] SM is synthesized by SM synthase (SMS) and SMS2 deficiency has shown decrease plasma membrane SM levels and attenuate NFκB activation both in macrophages and HEK293 cells. [ 19 ] Similarly, pharmacologic inhibition of SMS attenuated endotoxin‐mediated macrophage inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found strong correlations between plasma SM and IL‐6. [ 18 ] SM is synthesized by SM synthase (SMS) and SMS2 deficiency has shown decrease plasma membrane SM levels and attenuate NFκB activation both in macrophages and HEK293 cells. [ 19 ] Similarly, pharmacologic inhibition of SMS attenuated endotoxin‐mediated macrophage inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the body also reacts to gas explosion by avoiding oxidative damage and chronic inflammation, which may help reduce the severity of GEI. Chronic inflammation is an important factor of GEI [22] and could influence rat lipid metabolism [23]. The metabolism of cholesterol and phospholipids is a primary function of a normal rat liver, and downregulated synthesis of bile acids may lead to the malabsorption of lipids.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…The milk fat globule membrane (MFGM) is a unique triple‐membrane structure surrounding milk fat and contains many bioactive molecules. Previous studies found that both MFGM and several of its components, such as lactoferrin and sphingomyelin, might exert beneficial effects on intestinal barrier function 18‐20 . A recent study reported that MFGM supplementation promoted intestinal epithelium development in formula‐fed pups through increasing colonic Firmicutes abundance and MUC2 expression 21 .…”
Section: Introductionmentioning
confidence: 99%